MENTAL TOUGHNESS IN SPORT: TAILORING PSYCHOLOGICAL PREPAREDNESS FOR FEMALE FREESTYLE WRESTLING CHAMPIONS (American Journal of Interdisciplinary Research and Development, 2023)
This article delves into the realm of mental toughness in female freestyle wrestling, focusing on the essential psychological elements that can make the difference between a good athlete and a champion. Female freestyle wrestling demands a unique set of psychological skills and resilience. We explore the key aspects of mental toughness that female champions exhibit, including motivation, focus, emotional control, and resilience. Through interviews with elite female freestyle wrestlers and coaches, we uncover the specific strategies and mental training techniques that have proven to be effective in shaping the mindset of champions. By tailoring psychological preparedness for female freestyle wrestling champions, this article provides valuable insights for coaches, athletes, and sports psychologists aiming to nurture the mental fortitude required for success in this demanding and dynamic sport.